MicroRNAs-mediated regulation of the differentiation of dental pulp-derived mesenchymal stem cells: a systematic review and bioinformatic analysis - Pedram Iranmanesh; Amirhossein Vedaei; Sadra Salehi-Mazandarani; Parvaneh Nikpour; Saber Khazaei; Abbasali Khademi; Kerstin M. Galler; Mohammad-Hossein Nekoofar; Paul M. H. Dummer (Stem Cell Research & Therapy, 2023)
Abstract Background Human dental pulp-derived mesenchymal stem cells (hDP-MSCs), which include human dental pulp stem cells (hDPSCs) and stem cells from human exfoliated deciduous teeth (SHEDs), are promising cell sources for regenerative therapies. Nevertheless, a lack of knowledge relating to the mechanisms regulating their differentiation has limited their clinical application. microRNAs (miRNAs) are important regulatory molecules in cellular processes including cell differentiation. This systematic review aims to provide a panel of miRNAs that regulate the differentiation of hDP-MSCs including hDPSCs and SHEDs. Additionally, bioinformatic analyses were conducted to discover target genes, signaling pathways and gene ontologies associated with the identified miRNAs. Methods A literature search was performed in MEDLINE (via PubMed), Web of Science, Scopus, Embase and Cochrane Library. Experimental studies assessing the promotive/suppressive effect of miRNAs on the differentiation of hDP-MSCs and studies evaluating changes to the expression of miRNAs during the differentiation of hDP-MSCs were included. miRNAs involved in odontogenic/osteogenic differentiation were then included in a bioinformatic analysis. A miRNA-mRNA network was constructed, and Gene Ontology and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were performed. A protein–protein interaction (PPI) network was also constructed. Results Of 766 initially identified records through database searching, 42 and 36 studies were included in qualitative synthesis and bioinformatic analyses, respectively. Thirteen miRNAs promoted and 17 suppressed odontogenic/osteogenic differentiation of hDP-MSCs. hsa-miR-140-5p, hsa-miR-218 and hsa-miR-143 were more frequently reported suppressing the odontogenic/osteogenic differentiation of hDP-MSCs. hsa-miR-221 and hsa-miR-124 promoted and hsa-miR-140-5p inhibited neuronal differentiation, hsa-miR-26a-5p promoted and hsa-miR-424 suppressed angiogenic differentiation, and hsa-miR-135 and hsa-miR-143 inhibited differentiation within myogenic lineages. A miRNA-mRNA network including 1890 nodes and 2171 edges was constructed. KEGG pathway analysis revealed MAPK, PI3K-Akt and FoxO as key signaling pathways involved in the odontogenic/osteogenic differentiation of hDP-MSCs. Conclusions The findings of this systematic review support the potential application of the specific miRNAs to regulate the directed differentiation of hDP-MSCs in the field of regenerative therapies.